2021
DOI: 10.1080/20008198.2021.1875642
|View full text |Cite
|
Sign up to set email alerts
|

Saudi Arabia Mental Health Surveillance System (MHSS): mental health trends amid COVID-19 and comparison with pre-COVID-19 trends

Abstract: Background:The impact of the COVID-19 pandemic on populations' mental health has started to emerge. Objectives: To describe the mental health trends of the risk of major depressive disorder (MDD) and generalized anxiety disorder (GAD) between May and August 2020. It also compares the results with pre-COVID-19 results and identifies risk factors associated with increased likelihood of being at risk of MDD and GAD. Method: This study utilizes repeated cross-sectional design, at national-level coverage of mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 29 publications
5
65
0
1
Order By: Relevance
“…The reduction in physical activity was due to complete or partial lockdown, the closure of sports and fitness centers, and the increase in working from home, which all directly affect the attainment of the recommended physical activity levels. Fear of contracting COVID-19 may also have affected people’s willingness to go to fitness centers or attend group fitness activities, even after the end of the lockdown [ 4 ]. A recent systematic review exploring changes in physical activity and sedentary behaviors from before to during the pandemic stated that the majority of studies reported decreases in physical activity and increases in sedentary behaviors across several populations during their respective lockdowns, including in children and patients with a variety of medical conditions [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The reduction in physical activity was due to complete or partial lockdown, the closure of sports and fitness centers, and the increase in working from home, which all directly affect the attainment of the recommended physical activity levels. Fear of contracting COVID-19 may also have affected people’s willingness to go to fitness centers or attend group fitness activities, even after the end of the lockdown [ 4 ]. A recent systematic review exploring changes in physical activity and sedentary behaviors from before to during the pandemic stated that the majority of studies reported decreases in physical activity and increases in sedentary behaviors across several populations during their respective lockdowns, including in children and patients with a variety of medical conditions [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The indirect health effects of the COVID-19 pandemic and the responses to it can also be regarded as substantial [ 1 , 2 ]. The indirect effects may include denied or delayed disease prevention and medical procedures for acute and chronic conditions; reductions in awareness and educational public health campaigns for noncommunicable diseases; reduced physical activity [ 4 , 5 ]; losses of jobs and income and reductions in overall living status; disruption of social networks; increases in self-harm and anxieties over contracting the disease [ 4 ]; changes in the quantity and quality of food and overall diet; use of tobacco, alcohol and other drugs; changes in other infectious disease rates [ 1 , 2 ]. Such changes in the behavioral and intermediate risk factors related to noncommunicable diseases could significantly increase or decrease their prevalence in the population.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations